2017
DOI: 10.15761/fsc.1000119
|View full text |Cite
|
Sign up to set email alerts
|

Confabulation: A Beginner’s Guide for legal professionals

Abstract: Confabulation can be defined as the unintentional creation of a false or inaccurate memory to compensate for memory gaps or deficits. Although some similarities may exist, the phenomenon of confabulation is distinguishable from other issues like suggestibility, malingering, and delusions. The possibility of confabulation is particularly pernicious in criminal justice settings. Here, self-reported memories play an integral role in the confessions and testimony of suspects, defendants, victims, and eyewitnesses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 25 publications
0
14
0
8
Order By: Relevance
“…General Strain Theory further explains that one's social environment and their experiences (such as of child neglect, adverse life experiences, and a disjoined family structure) can create strain/tension which may result in that individual displaying deviant or criminal behavior as a form of survival (Agnew, 1985;Phuwachaijirapath et al, 2018). Research as to parricide in the global context has illustrated that, in general, perpetrators had been abused since childhood (Barber, 2020;Ewing, 1990;Heide, 2013;Kanyajit, 2014;Tang, 2019;Teche & Gomide, 2018;Viñas-Racionero et al, 2017;Rowe, 2006), regularly experienced domestic violence and altercations (Barber, 2020;Brown et al, 2017;Shon & Roberts, 2008;Teche & Gomide, 2018;Viñas-Racionero et al, 2017), and a history of alcohol/substance abuse (Heide, 2012). From these contexts, it has been found that weak social bonds, low levels of self-control, and significant mental or emotional strain are likely to be possessed here-factors which are understood to heighten the likelihood of parricide being committed without intention/ planning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…General Strain Theory further explains that one's social environment and their experiences (such as of child neglect, adverse life experiences, and a disjoined family structure) can create strain/tension which may result in that individual displaying deviant or criminal behavior as a form of survival (Agnew, 1985;Phuwachaijirapath et al, 2018). Research as to parricide in the global context has illustrated that, in general, perpetrators had been abused since childhood (Barber, 2020;Ewing, 1990;Heide, 2013;Kanyajit, 2014;Tang, 2019;Teche & Gomide, 2018;Viñas-Racionero et al, 2017;Rowe, 2006), regularly experienced domestic violence and altercations (Barber, 2020;Brown et al, 2017;Shon & Roberts, 2008;Teche & Gomide, 2018;Viñas-Racionero et al, 2017), and a history of alcohol/substance abuse (Heide, 2012). From these contexts, it has been found that weak social bonds, low levels of self-control, and significant mental or emotional strain are likely to be possessed here-factors which are understood to heighten the likelihood of parricide being committed without intention/ planning.…”
Section: Discussionmentioning
confidence: 99%
“…The location of such murders is usually a residence of the family (Anthony, 2014; Campion et al, 1985; Green, 1981; Heide, 2013; Mulvey et al, 2006). Parricide can occur when it has been pre-planned and an intention to kill is displayed (Trost, 2015; Wang, 2015) and when it is un-planned and happens without warning (Bourget et al, 2007; Brown et al, 2017). This crime may also be committed by one offender (Bromwich, 2017; Rowe, 2006) or with accomplices (Trost, 2015; Wang, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, over half of respondents either agreed or chose 'neither agree nor disagree' when asked if people can grow out of FASD. This is a gap in the knowledge essential for understanding FASD and accurately interpreting behaviours common among those with FASD (Brown et al, 2015;Fast & Conry, 2004, 2009. If staff do not know or understand that FASD constitutes lifelong, organic brain damage, they will have difficulty reframing an affected individual's behaviours and offering the required support (Fast & Conry, 2004, 2009Hughes & Peirse O'Byrne, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Konfabülasyon, aldatma niyeti olmaksızın hatalı bilgi üretme eylemidir. 12 Bu bilginin temeli, hafızadaki boşluklara, gerçek otobiyografik hatırlanmasında çarpıtmalara, olgusal bilginin elde edilmesinde yaşanan sorunlara veya gerçekte hiçbir temele dayanmayan anıların üretilmesine (fabrikasyon) dayanmaktadır. Hem genel populasyonda hem de ceza-adalet sisteminde konfabülasyonun yaygınlık oranı tam olarak bilinmemektedir.…”
unclassified
“…Bu nedenle, özellikle travmatik hafıza vakalarının ele alındığı yargılamalarda hukuk uygulayıcılarının bu olguyu göz ardı etmemesi önem arz etmektedir. 12,13 Modern psikolojinin en tartışmalı konularından biri olarak geri kazanılmış hatıra/sahte hatıra konusu adli psikoloji alanında da büyük önem taşımaktadır. 14 Bir kısım araştırmacılar geri kazanılmış hatıraların çocukluk çağı cinsel istismar olaylarında genellikle güvenilebilecek bir delil olduğunu ileri sürmektedirler.…”
unclassified